Byzantinische Kleinfunde aus Ephesos, Textband Ausgewählte Artefakte aus Metall, Bein und Glas - Pülz, Andrea M. (Verlag der Österreichischen Akademie der Wissenschaften, 2020)
The material legacy of Byzantine period from Ephesos includes, in addition to jewellery and dress accessories, liturgical artefacts, various instruments, tools and weapons, as well as small-scale implements including lighting devices, locks and keys.The declared aim of this study was a presentation of the Ephesian material as complete as possible including the manufacturing techniques and the material composition of individual objects. The interdisciplinary collaboration allowed to identify regional tendencies and local preferences as well as to compare the artefacts with other well-documented regions.Textband: https://e-book.fwf.ac.at/o:1415Katalog- und Tafelband: https://e-book.fwf.ac.at/o:1416